2013
DOI: 10.7314/apjcp.2013.14.6.3937
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of ER, PR, VEGF, CA15-3, CA125 and CEA in Judging the Prognosis of Breast Cancer

Abstract: Objective: To explore the expression and significance of estrogen receptor (ER), progestrone receptor (PR), vascular endothelial growth factor (VEGF), CA15-3, CA125 and carcinoma embryonic antigen (CEA) expression in judging the prognosis of breast cancer. Materials and Methods: Sixty-five patients with breast cancer undergoing operations in the general surgery department were considered as the observation group, and 50 healthy outpatients of our hospital as the control group. Cubital venous blood was drawn in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…The expression of CA15-3 increases significantly in most breast carcinomas (Frenette et al, 1994;Toth et al, 2008;Moazzezy et al, 2014). It was also shown that the rate of CA15-3 is correlated with tumor size, which reflects the stage of the disease (Clinton et al, 2003;Nicolini et al, 2008;Atoum et al, 2012;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CA15-3 increases significantly in most breast carcinomas (Frenette et al, 1994;Toth et al, 2008;Moazzezy et al, 2014). It was also shown that the rate of CA15-3 is correlated with tumor size, which reflects the stage of the disease (Clinton et al, 2003;Nicolini et al, 2008;Atoum et al, 2012;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a multifunctional cytokine that exerts a variety of effects on vascular endothelial cells that together promote the formation of new blood vessels, increases vascular endothelial permeability, stimulates the proliferation of endothelial cells and promote cancer cell progression (Dvorak, 2002;Mohammed et al, 2007;Niu et al, 2010;Akdeniz et al, 2013;Huang et al, 2013;Zhang et al, 2013). In particular, serum VEGF-A levels are elevated in patients with HNSCC compared to healthy controls (De Schutter et al, 2005;Hong et al, 2009;Liang et al, 2013).…”
Section: Serum Vascular Endothelial Growth Factor-a (Vegf-a) As a Biomentioning
confidence: 99%
“…It is well established that ER expression is linked to prognosis (Sofi et al, 2012;Zhang et al, 2013). Previous studies reported the proteomic profiles of ER + MCF7 and ER -MDA-MB-231 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%